A temperature spectrum density distribution based condition evaluation method and application in IGBT. (5th August 2016) - Gao, Bing; Yang, Fan; Chen, Minyou; Dong, Manling; Duan, Pan; Irfan, Ullah
Highlights: A temperature spectrum density based method for condition evaluation is presented. A 3D electric-thermal-mechanical model for IGBT module is set up. Experimental platform is built to verify the validation of the proposed method. Aged test and comparisons are investigated to validate the method further. The influences of Vdc, fsw on IGBT temperature spectrum density are studied. Abstract: Temperature measurement and calculation are frequently used in condition evaluation. In the paper, a temperature spectrum density method (TSDM) based on the statistic characteristics of thermal-image is proposed. Firstly, the temperature distribution of IGBT module for different condition was calculated, and based on the change of temperature distribution, the process for the TSDM is presented, including the building of temperature probability graph, calculation of kernel density, standard deviation (SD), temperature range (TR), and difference between peak and mean value. Examples analysis of IGBT were conducted, results indicate that the TSDM can track the condition change of IGBT module. Then, experimental investigation on the temperature spectrum density for different operation conditions were carried out, including the new and aged IGBT, and results demonstrate that temperature spectrum density changes with different conditions. Finally, influences of DC side voltage Vdc and switching frequency fsw were studied. It indicates that the temperature spectrum density parameters increase cubic polynomial with Vdc and linearly increase with switching frequency fsw .